Giving Questions and Getting Answers (GQGA) Strategy Improves Biology Learning Outcomes - Muhammad Eval Setiawan; Islaini Octiva Anggraeni (Scientiae Educatia: Jurnal Pendidikan Sains, 2019)
This study was intended to examine the effect of Giving Questions and Getting Answer (GQGA) learning strategy on the students’ biology learning outcomes at Al-Falah Islamic High School students in Jambi City. This research adopts a quantitative study using the true experiment design - posttest only control design. The instrument of data collection uses multiple-choice tests and observation sheets. From the data collection that has been obtained, the calculation resulted in the average value of the cognitive domain of the experimental class of 75.38 and the average affective domain of 77.38, while for the control class, the cognitive domain averaged 65.00 and the average affective domain of 71.03. Based on the results of data analysis, it was found that cognitive domain resulted in a value of t-count > t-table were 2.96 > 2.00 with the effect size 0.8 or 79% (a quite high category), while the affective domain was t-count > t-table which was 4.81 > 2.00 with the effect size 1.23 or 88% (high category). Based on these data, it shows that there is a significant effect on the use of the GQGA learning strategy on the students’ biology learning outcomes. The results of this study suggest teachers apply the GQGA Learning Strategy in biology learning, especially in the excretory system  material.